The Internship as a Catalyst for Civic Engagement: Using experiential education to depolarize the political climate. - Burwell, Rebecca; Huyser, Mackenzi; DeGraaf, Donald (Experiential Learning and Teaching in Higher Education, 2024)
In a time of record polarization and the questioning of the value of higher education, the internship plays an important and positive role in developing the civic minded graduate. Utilizing best practices in experiential education, an internship nurtures important civic skills in students and an orientation towards the common good. Through focus groups and surveys, our three-year research project found that internship sites and supervisors are integral partners in nurturing a student's ability to engage their communities. An internship, as an incubator for civic skills, is a valuable educational contribution to society.